How do Poles binge-watch? : Binge-watching before and during the pandemic - a representative study - Jupowicz-Ginalska, Anna; Kisilowska-Szurmińska, Małgorzata; Szurmiński, Łukasz (Media - Culture - Social Communication, 2024)
Binge-watching is a relatively new form of consuming media content, which has found a permanent place in the set of viewers’ media consumption behaviours. The aim of this project was to identify the scale and diversity of binge-watching among Polish Internet users. The study was conducted using the quantitative method (CAWI) on a representative group of Polish Internet users in two cycles – in 2020 and 2021. The respondents were asked, for example, whether they binge-watched, and if they did, what they watched and whether the pandemic had an impact on their behaviour as viewers. The results indicate the scale of binge-watching, the preferred types of content and the potential impact of the pandemic on the behaviour under study. Thus, the first full, representative picture of binge-watching among Polish Internet users was obtained.